EU competition law: An unaffordable luxury in times of crisis? - Patrick Massey; Moore McDowell (University College Dublin, UCD Centre for Economic Research, 2020)
The paper looks at two aspects of the Covid-19 pandemic. These are (i) the nature of this event and its implication for evaluating past policy and policy into the future, and (ii) the suitability of proposed changes in the implementation of competition policy affecting firm behaviour, market structures and state intervention. The first conclusion the paper reaches is that it is incorrect to describe the Covid-19 pandemic as a "Black Swan" event, unpredicted and unpredictable, and something for which it is not possible to prepare. Policy makers should accept responsibility for possible future events such as pandemics even when timing is uncertain. In the case of Covid-19, policy measures were clearly inadequate. The paper then considers the design and implementation of measures aimed at supporting economic recovery. The arguments that competition policy should be relaxed for the duration of the problem is rejected as ill-founded and counterproductive. In particular, it is wrong to treat the response to the Financial Crisis of 2008-2011 as justifying reduced competition in general. Some aspects of particular policy designs, decisions and actions in response to the recession flowing from the medical response to Covid-19 are subjected to critical analysis.
Keywords: I15; I18; 330; COVID-19; Economic recovery